Association between coping skills, past injury and hip pain and function in adolescent elite female ballet dancers - Biernacki, J. L.; Stracciolini, A.; Griffith, K. L.; D`Hemecourt, P. A.; Owen, M.; Sugimoto, D. (The Physician and Sportsmedicine, 2018)
Objectives: The purpose of this study was to investigate the relationship between coping skills and current hip pain and function scores in ballet dancers. Secondly, we examined the relationship between coping skills and past injuries. Thirdly, we investigated the association between past injuries and current pain and function scores.